2015
DOI: 10.1007/s12010-015-1932-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced H2 Production and Redirected Metabolic Flux via Overexpression of fhlA and pncB in Klebsiella HQ-3 Strain

Abstract: Genetic modifications are considered as one of the most important technologies for improving fermentative hydrogen yield. Herein, we overexpress fhlA and pncB genes from Klebsiella HQ-3 independently to enhance hydrogen molar yield. HQ-3-fhlA/pncB strain is developed by manipulation of pET28-Pkan/fhlA Kan(r) and pBBR1-MCS5/pncB Gm(r) as expression vectors to examine the synchronous effects of fhlA and pncB. Optimization of anaerobic batch fermentations is achieved and the maximum yield of biohydrogen (1.42 mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…aerogenes [24,25], Enterobacter sp. CN1 [26], and Klebsiella HQ-3 [27], which has increased hydrogen production to some extent. However, these bacteria only utilized the synthetic medium for hydrogen production, or adding formic acid to promote hydrogen evolution.…”
Section: Discussionmentioning
confidence: 99%
“…aerogenes [24,25], Enterobacter sp. CN1 [26], and Klebsiella HQ-3 [27], which has increased hydrogen production to some extent. However, these bacteria only utilized the synthetic medium for hydrogen production, or adding formic acid to promote hydrogen evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Photo-autotrophic microorganisms like cyanobacteria or green microalgae used the method of bio-photolysis that possess chlorophyll A and other pigments and has a capacity to capture sunlight and split water to make H 2 . Even though, there are some barriers in this method such as: the O 2 evolved during this method suppresses the activation of hydrogenase subunits, gas mixture formed during the process is combustible, low photosynthetic conversion efficiencies and large surface area requirement engineering of biological systems for improvement in BHP [3], [4]. A precise genome-scale model of an organism helps us in studying the effect of environmental and genetic limitations on it, and hence these facts motivate experiments in the area of metabolic engineering.…”
Section: Methods For Biohydrogen Productionmentioning
confidence: 99%
“…Nevertheless, research on the FHL complex in other species of the Enterobacter genus is still limited; only a few studies have reported fhlA gene expression in Enterobacter aerogenes [22], Enterobacter sp. CN1 [23] and Klebsiella HQ-3 [24], whereas the fhlA gene of Enterobacter cloacae and its expression have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%